2006
DOI: 10.1016/j.neurobiolaging.2005.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Markers of inflammation, Vitamin E and peripheral nervous system function

Abstract: Our findings are consistent with the hypothesis that inflammation and inadequate antioxidant defenses are associated with accelerated decline of nerve conduction velocity over the aging process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
4
35
0
1
Order By: Relevance
“…Likewise, the peripheral nerve measurements were represented by "Peripheral Nerve Function", and the tapping test and Short Blessed mental test were together represented by "Central Nervous System Function". Age exerted a direct influence on Glucose120, Inflammatory Markers, Peripheral Nerve Function, height and Central Nervous System function [5,6,29,30,32]. When the mediating effect of these variables was accounted for, we found no residual direct effect of age on vibration threshold.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Likewise, the peripheral nerve measurements were represented by "Peripheral Nerve Function", and the tapping test and Short Blessed mental test were together represented by "Central Nervous System Function". Age exerted a direct influence on Glucose120, Inflammatory Markers, Peripheral Nerve Function, height and Central Nervous System function [5,6,29,30,32]. When the mediating effect of these variables was accounted for, we found no residual direct effect of age on vibration threshold.…”
Section: Discussionmentioning
confidence: 66%
“…Studies performed on cell culture have demonstrated that the costimulation of Tumor Necrosis Factor -α Receptor1 (TNF-αR1) and Tumor Necrosis Factor -α Receptor2 (TNF-αR2) is a powerful pro-apoptotic stimulus [10]. Further, using data from a large population-based study, Di Iorio et al [6] have recently reported a significant inverse association between peroneal nerve conduction velocity and circulating levels of serum Interleukin-6 Receptor (sIL-6R). Thus, it is reasonable to hypothesize that the mild pro-inflammatory state that is often encountered in older adults may account, at least in part, for the progressive decline of vibrotactile sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…These results are of particular interest in the context of data from InCHIANTI, a population-based study in Italy, which reported associations of higher IL6 and sIL-6R levels with reduced peroneal MNCV (27). Furthermore, an association of higher IL6 with reduced sural and peroneal NAPs was observed in a small study (7).…”
Section: Subclinical Inflammation Dspn and Ncv In Type 2 Diabetesmentioning
confidence: 60%
“…Interestingly, one large population-based study indicated that circulating levels of the soluble IL6 receptor (sIL-6R) may be inversely associated with peroneal motor NCV (MNCV) (27).…”
mentioning
confidence: 99%
“…However, the crosssectional design of almost all clinical and epidemiological studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) so far precludes inferences regarding the temporal relationship between inflammation and DSPN, which are essential for any conclusions about causality. One small prospective study assessed plasma levels of soluble adhesion molecules in 28 individuals with diabetes during a 5-year study period and suggested that endothelial activation is associated with nerve conduction slowing (18).…”
mentioning
confidence: 99%